Integral - Sum- Golden ratio

Calculus Level 3

1 ( 1 3 φ n + 2 3 φ 2 n 3 3 φ 3 n + 4 3 φ 4 n 5 3 φ 5 n + ) d n = a b ( a + b ) log φ \int_ 1^\infty \left(-\frac {1^3}{\varphi^n} + \frac {2^3}{\varphi^{2n}} - \frac {3^3}{\varphi^{3n}} + \frac {4^3}{\varphi^{4n}} - \frac {5^3}{\varphi^{5n}} + \cdots \right) dn = \frac {a\sqrt b-(a+b)}{\log \varphi}

If the equation above holds true for integers a a and b b with b b being square-free, find b a b-a .

Notation: φ = 1 + 5 2 \varphi = \dfrac {1+\sqrt 5}2 denotes the golden ratio .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
May 21, 2020

I = 1 k = 1 ( 1 ) k k 3 φ k n d n = k = 1 ( 1 ) k k 2 φ k log φ Replace 1 φ with x . = x log φ d d x ( x d d x 1 1 + x ) = x log φ d d x ( x ( x + 1 ) 2 ) = x log φ x 1 ( x + 1 ) 3 Replace x with 1 φ . = φ 1 log φ φ 1 1 ( φ 1 + 1 ) 3 Note that 1 φ = φ 1 = 1 log φ 1 φ φ 5 = 1 φ 6 log φ and φ n = F n φ F n 1 = 1 log φ ( 8 φ + 5 ) = 2 log φ ( 8 5 + 18 ) = 4 5 9 log φ \begin{aligned} I & = \int_1^\infty \sum_{k=1}^\infty \frac {(-1)^k k^3}{\varphi^{kn}} dn \\ & = \sum_{k=1}^\infty \frac {(-1)^k k^2}{\varphi^k \log \varphi} & \small \blue{\text{Replace }\frac 1\varphi \text{ with }x.} \\ & = \frac x{\log \varphi} \cdot \frac d{dx} \left(x \cdot \frac d{dx} \cdot \frac 1{1+x} \right) \\ & = \frac x{\log \varphi} \cdot \frac d{dx} \left(-\frac x{(x+1)^2} \right) \\ & = \frac x{\log \varphi} \cdot \frac {x-1}{(x+1)^3} & \small \blue{\text{Replace }x \text{ with } \frac 1\varphi .} \\ & = \frac {\varphi^{-1}}{\log \varphi} \cdot \frac {\varphi^{-1}-1}{(\varphi^{-1}+1)^3} & \small \blue{\text{Note that }\frac 1\varphi = \varphi - 1} \\ & = \frac 1{\log \varphi} \cdot \frac {1-\varphi}{\varphi^5} = - \frac 1{\blue{\varphi^6}\log \varphi} & \small \blue{\text{and }\varphi^n = F_n\varphi - F_{n-1}} \\ & = -\frac 1{\log \varphi(8\varphi +5)} = - \frac 2{\log \varphi(8\sqrt 5+18)} \\ & = \frac {4\sqrt 5 - 9}{\log \varphi} \end{aligned}

Therefore b a = 5 4 = 1 b-a = 5-4 = \boxed 1 .

well done.

Srinivasa Raghava - 1 year ago

Log in to reply

Glad that you like it. I have solved your previous one involving gamma function

Chew-Seong Cheong - 1 year ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...